The diagnostic use of magnetic resonance imaging for acute abdominal and pelvic pain in pregnancy. (March 2020) - Tarannum, Asma; Sheikh, Haifa; Appiah-Sakyi, Kwabena; Lindow, Stephen W.
Abstract: Objectives: Acute abdomino-pelvic pain in pregnancy represents a diagnostic challenge. In many cases, radiological and laparoscopic diagnostic modalities are hazardous or contraindicated. Magnetic Resonance Imaging (MRI) is not commonly used for this indication and the results are not widely published. Design and setting: A single-center retrospective observational study. Population: 34 cases of pregnant women with abdomino-pelvic pain who underwent MRI as an additional modality when clinical, laboratory and ultrasound (USS) findings were indeterminate. Methods: Case notes were reviewed where pregnant women underwent a MRI investigation for abdominal-pelvic pain. Primary Obstetric indications for an MRI eg placenta accreta were excluded. Main outcome measures: The differential diagnosis after; 1) history and physical examination and 2) with the addition of USS and 3) with the further addition of an MRI were all individually compared to the eventual diagnosis. Results: The diagnoses reached by MRI corresponded with the final diagnosis in 22 out of 23 cases. In the remaining 11 cases MRI accurately ruled out presence of pathology. MRI was inaccurate in 1 case. Conclusion: The additional use of MRI was more accurate than clinical assessment and USS combined. The accurate exclusion of pathology in 11 cases is particularly significant. MRI should be considered in cases of abdomino-pelvic pain in pregnant women.